2015
DOI: 10.3389/fchem.2015.00048
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials in consumer products: a challenging analytical problem

Abstract: Many products used in everyday life are made with the assistance of nanotechnologies. Cosmetic, pharmaceuticals, sunscreen, powdered food are only few examples of end products containing nano-sized particles (NPs), generally added to improve the product quality. To evaluate correctly benefits vs. risks of engineered nanomaterials and consequently to legislate in favor of consumer's protection, it is necessary to know the hazards connected with the exposure levels. This information implies transversal studies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
114
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(118 citation statements)
references
References 139 publications
0
114
0
Order By: Relevance
“…nSP were introduced into food and consumer products in the 1990s, and are used as anticaking agents in food powders; in health-care products such as toothpastes, detergents, and cosmetics; as stabilizers and clarifying agents in liquors; and as antifoaming agents in the manufacture of decaffeinated coffee and tea (Contado 2015). A recent study demonstrated that orally administered amorphous nSP penetrate the intestinal barrier (Yoshida et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…nSP were introduced into food and consumer products in the 1990s, and are used as anticaking agents in food powders; in health-care products such as toothpastes, detergents, and cosmetics; as stabilizers and clarifying agents in liquors; and as antifoaming agents in the manufacture of decaffeinated coffee and tea (Contado 2015). A recent study demonstrated that orally administered amorphous nSP penetrate the intestinal barrier (Yoshida et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…42 Applications capitalizing on the unique ability of TiO 2 NPs to form ROS under UV light irradiation are of particular interest. However, UV light is damaging and repeated exposure has been linked to skin damage and tumors caused directly by UV irradiation and indirectly through oxidative stress mechanisms and uncontrolled ROS formation.…”
Section: Biocompatibility and Antibacterial Activity Of N-tio 2 Npsmentioning
confidence: 99%
“…Several highlighted some current applications of nanomaterials in food, food additives and food-contact materials, and reviewed analytical approaches suitable to address food-safety issues related to nanotechnology [21][22][23][24][25][26]. These previous studies showed the difficulty of the analysis, the lack of proper methodologies and the need of different techniques' combination as well as the rapid advances within this area.…”
Section: Article In Pressmentioning
confidence: 99%